A century of homoeopathic paediatrics - Leary, Bernard (British Homeopathic Journal, 1995)
Among homoeopaths the idea of specialist provision for children followed the general trend. It was encouraged by the high morbidity and mortality among children due to poverty. The prevalence of tuberculosis, syphilis and the infectious fevers, together with the ignorance about hygiene of mothers of young children, were all factors of concern. Homoeopathic physicians and their supporters wished to give poor children the benefits of their system, which they believed could deal more efficaciously with the risks to their health. Homoeopathic specialist units gradually disappeared, partly due to the NHS and partly because the factors which stimulated their inception no longer applied. Homoeopathy itself became the speciality.
Keywords: History of homoeopathy; Paediatrics; Children; Dispensary